2006
DOI: 10.1105/tpc.106.046326
|View full text |Cite
|
Sign up to set email alerts
|

Protein Polyubiquitination Plays a Role in Basal Host Resistance of Barley

Abstract: To study protein ubiquitination pathways in the interaction of barley (Hordeum vulgare) with the powdery mildew fungus (Blumeria graminis), we measured protein turnover and performed transient-induced gene silencing (TIGS) of ubiquitin and 26S proteasome subunit encoding genes in epidermal cells. Attack by B. graminis hyperdestabilized a novel unstable green fluorescent protein fusion that contains a destabilization domain of a putative barley 1-aminocyclopropane-1-carboxylate synthase, suggesting enhanced pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 36 publications
2
53
0
Order By: Relevance
“…Nevertheless, we controlled for this possibility by assessing the ability of alternate BEC1054 and BEC1011 coding constructs with no possible targeting by the RNAi constructs (Dong et al 2006;Nowara et al 2010) to complement the phenotypes that resulted from the HIGS constructs. Co-bombardment of these wobble constructs with their respective HIGS constructs did not affect the HI, indicating that the effect of the HIGS constructs alone on HI is, indeed, dependent on the direct silencing of the respective BEC.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we controlled for this possibility by assessing the ability of alternate BEC1054 and BEC1011 coding constructs with no possible targeting by the RNAi constructs (Dong et al 2006;Nowara et al 2010) to complement the phenotypes that resulted from the HIGS constructs. Co-bombardment of these wobble constructs with their respective HIGS constructs did not affect the HI, indicating that the effect of the HIGS constructs alone on HI is, indeed, dependent on the direct silencing of the respective BEC.…”
Section: Discussionmentioning
confidence: 99%
“…Partial depletion of ubiquitin levels by transient-induced silencing of the ubiquitin-encoding gene in barley (Hordeum vulgare) epidermal cells resulted in enhanced susceptibility to the powdery mildew fungus Blumeria graminis f. sp. hordei (Dong et al, 2006). Moreover, complementation studies suggested a role for Lys-48-linked polyubiquitination in defense signaling (Dong et al, 2006).…”
Section: Ubiquitin and 26s Proteasomal Componentsmentioning
confidence: 99%
“…Importantly, transformation of ror2 with the ARFA1b-T31N construct had no additional effect on the frequency of cells with haustoria ( Figure 3), implying that ROR2 and ARFA1b/1c act on the same pathway. To rule out the possibility that a penetration maximum already is reached in ror2 and that this is the reason why no further increase in cells with haustoria was observed after transformation with ARFA1b-T31N, we silenced polyubiquitin, previously found to dramatically affect penetration resistance in barley (Dong et al, 2006). The polyubiquitin RNAi construct increased the frequency of cells with haustoria in ror2 by 2.7-fold, showing that a penetration maximum had not been reached (Figure 3).…”
Section: Arfa1b/1c Is Required For Ror2-mediated Penetration Resistancementioning
confidence: 99%
“…The Ubq RNAi construct was generated from a polyubiquitin EST sequence in the pDNR-LIB vector (BD Biosciences). The EST was derived from the same gene as HO13K06 used by Dong et al (2006). A PCR fragment of this polyubiquitin sequence, amplified using a gene-specific (Hv Ubq) and a vector-specific primer (Universal forward) (see Supplemental Table 2 online), was inserted into the entry vector pIPKTA38 according to Douchkov et al (2005).…”
Section: Amplification Of Arf-gtpase Coding Sequences and Preparationmentioning
confidence: 99%